Spesies Meloidogyne penyebab umbi berbintil kentang pada tiga sentra produksi di Sumatra - Hamidi, Ilmi; Supramana; Mutaqin, Kikin Hamzah; Kurniawati, Fitrianingrum (Jurnal Fitopatologi Indonesia, 2022)
Meloidogyne species, the pimple-like knot pathogen of potato tuber in three production centers in SumatraThe root-knot nematode (Meloidogyne spp.) is the cause of pimple-like swelling symptoms, which results in a decrease in the quality and quantity of potato production in the Sumatra region. Identification of the Meloidogyne species is necessary for designing its effective control strategies. This study aimed to detect and identify Meloidogyne species in potatoes morphologically, morphometry, and molecularly. Potato tubers with pimple-like swelling symptoms, tuber shape malformations, uneven tuber surface, and corrugated tuber surface were collected from 3 potato production centers in Sumatra, i.e., Karo (North Sumatra), Solok (West Sumatra), and Kerinci (Jambi). Nematode extraction was conducted by a surgical technique of spotted tuber tissue. Morphological identification was conducted based on the perineal patterns of females. Morphometric measurements were carried out on juvenile 2 based on the de Man formula. Molecular identification was conducted by PCR technique, followed by nucleotide sequencing and phylogenetic analysis. Three species of Meloidogyne identified were Meloidogyne arenaria, M. incognita, and M. javanica. DNA amplification using a CO1-specific primer successfully amplified DNA bands of ±360 bp for M. arenaria, ±326 bp for M. incognita, and ±170 bp for M. javanica. The sequencing results showed that M. incognita isolates from Karo-Indonesia were very closely related to M. incognita isolates from China, the United States, Vietnam, the United Kingdom, Brazil, and South Africa. M. javanica isolates from Solok-Indonesia were very closely related to M. javanica from the United States, Africa, China, Germany, and the United Kingdom.